2001
DOI: 10.1007/s003350010218
|View full text |Cite
|
Sign up to set email alerts
|

Genetic architecture of adiposity in the cross of LG/J and SM/J inbred mice

Abstract: The genetic basis of variation in obesity in human populations is thought to be owing to many genes of relatively small effect and their interactions. The LG/J by SM/J intercross of mouse inbred strains provides an excellent model system in which to investigate multigenic obesity. We previously mapped a large number of quantitative trait loci (QTLs) affecting adult body weight in this cross. We map body composition traits, adiposity, and skeletal size, in a replicate F2 intercross of the same two strains conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
183
5

Year Published

2002
2002
2012
2012

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 146 publications
(203 citation statements)
references
References 69 publications
15
183
5
Order By: Relevance
“…The estimated location of this QTL is proximal to that of the QTL described in this study, and the confidence intervals from the two studies only just overlap. The Chr 1 QTL described by Cheverud et al (2001) affects tail length in both sexes, as in this study, but does not have an effect on body mass at 10 weeks of age, consistent with the relatively weak or non-significant effects on body mass observed in this study. Klingenberg et al (2001) and performed genome-wide scans for QTL affecting mandible size and femur length, respectively (among other traits), but did not detect QTL for these traits on Chr 1.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The estimated location of this QTL is proximal to that of the QTL described in this study, and the confidence intervals from the two studies only just overlap. The Chr 1 QTL described by Cheverud et al (2001) affects tail length in both sexes, as in this study, but does not have an effect on body mass at 10 weeks of age, consistent with the relatively weak or non-significant effects on body mass observed in this study. Klingenberg et al (2001) and performed genome-wide scans for QTL affecting mandible size and femur length, respectively (among other traits), but did not detect QTL for these traits on Chr 1.…”
Section: Discussionsupporting
confidence: 88%
“…In an intercross between two inbred strains selected for high and low body size, Cheverud et al (2001) identified seven QTL affecting tail length, one of which was located on Chr 1. The estimated location of this QTL is proximal to that of the QTL described in this study, and the confidence intervals from the two studies only just overlap.…”
Section: Discussionmentioning
confidence: 99%
“…The probability associated with the multiple regression at each QTL position was transformed to a linear scale by logarithmic transformation [LPR = log 10 (1/Prob.)] (see Cheverud et al, 2001) and, as a result, our LPR scores can be directly compared to LOD scores obtained through maximum likelihood methods (Lander and Botstein, 1989). Environmental covariates were included in the mapping to remove phenotypic variation.…”
Section: Quantitative Geneticsmentioning
confidence: 99%
“…The 5% chromosome-wide significance levels were obtained by dividing 0.05 by the effective number of markers on that chromosome. For a discussion of the merits of using a chromosome wide significance level see Cheverud et al (2001). The genome-wide significance level was obtained by dividing 0.05 by the effective number of markers in the genome.…”
Section: Quantitative Geneticsmentioning
confidence: 99%
See 1 more Smart Citation